Luminance Calibration and Linearity Correction Method of Imaging Luminance Measurement Devices - Czyżewski, Dariusz; Fryc, Irena (Photonics Letters of Poland, 2021)
This paper presents that the opto-electrical characteristic of a typical CCD based digital camera is nonlinear. It means that digital electric signal of the camera’s CCD detector - is not a linear function of the luminance value on camera’s lens. The opto-electrical characteristic feature of a digital camera needs to be transformed into a linear function if this camera is to be used as a luminance distribution measurement device known as Imaging Luminance Measurement Device (ILMD). The article presents the methodology for obtaining the opto-electrical characteristic feature of a typical CCD digital camera and focuses on the non- linearity correction method. Full Text: PDF References D. Wüller and H. Gabele, "The usage of digital cameras as luminance meters," in Digital Photography III, 2007, p. 65020U CrossRef P. Fiorentin and A. Scroccaro, "Detector-Based Calibration for Illuminance and Luminance Meters-Experimental Results," IEEE Transactions on Instrumentation and Measurement, vol. 59, no. 5, pp. 1375-1381, 2010 CrossRef M. Shpak, P. Kärhä, G. Porrovecchio, M. Smid, and E. Ikonen, "Luminance meter for photopic and scotopic measurements in the mesopic range," Meas. Sci. Technol, vol. 25, no. 9, p. 95001, 2014, CrossRef P. Fiorentin, P. Iacomussi, and G. Rossi, "Characterization and calibration of a CCD detector for light engineering," IEEE Transactions on Instrumentation and Measurement, vol. 54, no. 1, pp. 171-177, 2005, CrossRef I. Fryc and E. Czech, "Application of optical fibers and CCD array for measurement of luminance distribution," in Proc. SPIE 5064, Lightmetry 2002: Metrology and Testing Techniques Using Light, 2003, pp. 18-21, CrossRef I. Fryc, "Accuracy of spectral correction of a CCD array for luminance distribution measurement," in Proc. SPIE 5064, Lightmetry 2002: Metrology and Testing Techniques Using Light, 2003, pp. 38-42, CrossRef I. Fryc, "Analysis of the spectral correction errors of illuminance meter photometric head under the influence of the diffusing element," Optical Engineering, vol. 40, no. 8, pp. 1636-1640, 2001. CrossRef D. Czyzewski, "Monitoring of the subsequent LED lighting installation in Warsaw in the years 2014-2015," in Proceedings of 2016 IEEE Lighting Conference of the Visegrad Countries, Lumen V4 2016, 2016, pp. 1-4, CrossRef M. Sielachowska, D. Tyniecki, and M. Zajkowski, "Measurements of the Luminance Distribution in the Classroom Using the SkyWatcher Type System," in 2018 VII. Lighting Conference of the Visegrad Countries (Lumen V4), 2018, pp. 1-5, CrossRef W. Malska and H. Wachta, "Elements of inferential statistics in a quantitative assessment of illuminations of architectural structures," in 2016 IEEE Lighting Conference of the Visegrad Countries (Lumen V4), 2016, pp. 1-6, CrossRef T. Kruisselbrink, R. Dangol, and A. Rosemann, "Photometric measurements of lighting quality: An overview," Building and Environment, vol. 138, pp. 42-52, 2018. CrossRef A. Borisuit, M. Münch, L. Deschamps, J. Kämpf, and J.-L. Scartezzini, "A new device for dynamic luminance mapping and glare risk assessment in buildings," in Proc. SPIE 8485. Nonimaging Optics: Efficient Design for Illumination and Solar Concentration IX, 2012, vol. 8485, p. 84850M, CrossRef I. Lewin and J. O’Farrell, "Luminaire photometry using video camera techniques," Journal of the Illuminating Engineering Society, vol. 28, no. 1, pp. 57-63, 1999, CrossRef D. Czyżewski, "Research on luminance distributions of chip-on-board light-emitting diodes," Crystals, vol. 9, no. 12, pp. 1-14, 2019, CrossRef K. Tohsing, M. Schrempf, S. Riechelmann, H. Schilke, and G. Seckmeyer, "Measuring high-resolution sky luminance distributions with a CCD camera," Applied optics, vol. 52, no. 8, pp. 1564-1573, 2013. CrossRef D. Czyzewski, "Investigation of COB LED luminance distribution," in Proceedings of 2016 IEEE Lighting Conference of the Visegrad Countries, Lumen V4 2016, 2016, pp. 1-4, CrossRef A. de Vries, J. L. Souman, B. de Ruyter, I. Heynderickx, and Y. A. W. de Kort, "Lighting up the office: The effect of wall luminance on room appraisal, office workers’ performance, and subjective alertness," Building and Environment, 2018 CrossRef D. Silvestre, J. Guy, J. Hanck, K. Cornish, and A. Bertone, "Different luminance- and texture-defined contrast sensitivity profiles for school-aged children," Nature. Scientific Reports, vol. 10, no. 13039, 2020, CrossRef H. Wachta, K. Baran, and M. Leśko, "The meaning of qualitative reflective features of the facade in the design of illumination of architectural objects," in AIP Conference Proceedings, 2019, vol. 2078, no. 1, p. 20102. CrossRef CIE, "Technical raport CIE 231:2019. CIE Classification System of Illuminance and Luminance Meters.," Vienna, Austria, 2019. CrossRef DIN, "Standard DIN 5032-7:2017. Photometry - Part 7: Classification of illuminance meters and luminance meters.," 2017. DirectLink CEN, "EN 13032-1:2004. Light and lighting - Measurement and presentation of photometric data of lamps and luminaires - Part 1: Measurement and file format," Bruxelles, Belgium., 2004. DirectLink CIE, "Technical raport CIE 231:2019. CIE Classification System of Illuminance and Luminance Meters," Vienna, Austria, 2019 CrossRef E. Czech, D. Czyzewski, "The linearization of the relationship between scene luminance and digital camera output levels", Photonics Letter of Poland 13, 1 (2021). CrossRef